Analisis Perubahan Tutupan Lahan Kabupaten Karo - Arie Yerikho Ginting; Siti Latifah; Rahmawaty Rahmawaty (Program studi Kehutanan USU, 2012)
Land use and land cover is an important component in understanding the interaction of human activities with the environment. Forest management include the planning and supervision in the Karo regency forest becomes very important to do in order to prevent degradation of the forest more severe. The purpose of this study was to quantify changes in land use from 1997 to 2012 and makes predictions extensive land use in 2018 and 2024. This research methods to utilize remote sensing technology and geographic information systems (GIS) and then compare the 5 maps of land use interpretation of Landsat ETM + (1997, 2000, 2003, 2006 and 2009 ). Classification results show that the Karo Regency has 11 land cover classes. The equation obtained from the linear regressions used to predict land cover area.The results showed that widespread changes in land cover occurred in dryland farming into rice paddies. Therefore, it is necessary that proper spatial planning in Karo Regency. Key word : land use change, land cover, landsat ETM+ image